Effects of Mastery Learning Instruction on Engineering Students' Writing Skills Development and Motivation - Amare Tesfie Birhan (National Research University Higher School of Economics, 2018)
This study was aimed to investigate the effects of mastery learning instruction on engineering students' academic writing skills and motivation in an EFL context. The participants were software engineering and computer science first-year students, and they were selected using a multistage sampling technique. Observation, a questionnaire, and pre- and post-tests were employed as data gathering instruments. The research was designed through a time series quasi-experimental research design. The data were analysed through repeated measure ANOVA, independent t-tests, as well as descriptive statistics. The findings indicated that there was a statistical difference between the experimental and the control groups. Hence, students who participated in mastery learning instruction improved their writing skills and achieved better scores in writing skills assessment. Particularly, learners who learned through mastery learning instruction were able to develop paragraphs and essays with clear topic sentences and thesis statements. They also developed paragraphs with proper punctuation and minimized various mechanical errors that were observed during the pre-test. Furthermore, the students who engaged in mastery learning instruction had better levels of motivation. Thus, individualized instruction and continuous feedback helped them improve their engagement in writing activities. Hence, this study calls for more attention to self-paced instruction, regular feedback, assessment, and continuous support in writing classrooms.